Towards a data-driven financial system: The impact of COVID-19 - REMOLINA LEON, Nydia (Institutional Knowledge at Singapore Management University, 2022)
The coronavirus disease (COVID-19) outbreak has had a growing impact on the global economy and the financial sector. Given the unprecedented macroeconomic nature of the crisis, financial regulators and central banks, along with governments and legislatures, face challenges to maintain financial stability, preserve the core markets, and ensure the flow of credit to the real economy. The financial sector has not only implemented these measures but has also adapted to the new circumstances derived from the pandemic. In this process, the ongoing digital transformation of the financial industry helped to address some of the emerging challenges. Indeed, the digital financial infrastructure that emerged in the wake of the 2008 global financial crisis is being, and can be, leveraged to overcome the immediate challenges presented by the pandemic and manage the impending economic fallout. The first section of the chapter describes the data-driven transformation of the financial services industry, a growing phenomenon within the financial technology (fintech) space.